Strategic Management of Environmental, Social, and Governance Scores and Corporate Governance Index: A Panel Data Analysis of Firm Value on the Istanbul Stock Exchange - Yucel, Mustafa; Yanik, Guler; Dayi, Faruk; Benek, Ayhan (MDPI AG, 2025)
This study investigates how Environmental, Social, and Governance (ESG) scores and the Corporate Governance Index (CGI) jointly influence firm value in Türkiye. To address the contextual limitations of global ESG metrics, this study incorporates the CGI, a country-specific governance measure developed by Capital Markets Board of Türkiye, as a complementary indicator. Using panel data from 44 non-financial firms listed on the Istanbul Stock Exchange between 2019 and 2023, the study applies a random effects regression model with robust standard errors. The findings indicate that both ESG and CGI scores are positively and significantly associated with firm value, along with profitability (ROA), while financial leverage and liquidity (CR) show negative effects. The results underscore the strategic value of aligning sustainability performance with governance quality, particularly in emerging market contexts. This study contributes to the literature by providing empirical evidence for an integrated ESG–CGI framework and offers practical insights for corporate managers, investors, and policymakers.
Keywords: Corporate governance; Strategic management; Sustainability; ESG; CGI; Firm value